Hubungan Kreativitas Mengajar Guru dan Minat Belajar Terhadap Hasil Belajar IPA pada Siswa Kelas VI SD Advent 01 Tikala Manado - Trinansi D. Makausi; Joulanda A.M. Rawis; Supit Pusung; Jeanne Mangangantung; Mersty Rindengan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the relationship between teacher teaching creativity and learning outcomes in Natural Sciences in grade VI elementary school students, to determine the level of creativity in teaching teachers and the level of interest in learning Natural Sciences at grade VI elementary school students, and to find a relationship between teaching creativity learning. teachers, interest in learning and learning outcomes of Natural Sciences in grade VI elementary school students. This study uses a descriptive survey method with descriptive statistics to describe the data from the collected sample to make a generalization. The results showed that there was a significant relationship between teaching creativity and learning outcomes in Natural Sciences for grade VI elementary school students. Based on the results of the analysis in table 4.9, it was obtained Tcount = 3595 T table with a significant level = 0.05, with numerator = 2 and denominator = 69 obtained T table = 2,000. It turns out that the value of Tcount is 3595 > 2,000 Ttable, then there is a relationship between student interest in learning and learning outcomes in Natural Sciences for grade VI elementary school students. 69 obtained T table = 2,000. It turns out that the value of Tcount is 7,840 > 2,000 Ttable, and there is a significant relationship between teaching creativity and students' interest in learning together with learning outcomes in Natural Sciences for grade VI elementary school students. significance level of 0.000 and 0.000 <0.05.